The effect of mixed diluent on the porous structure of crosslinked PMMA beads - Aykurt, M; Küçük, I; Kuyulu, A (SPRINGER VERLAG, 2000)
In this work copolymer beads, based on MMA (methyl methacrylate) and EGDM (ethylene glycol dimethacrylate), were prepared by suspension polymerization. A mixed solvent, composed of two different solvents, namely toluene and cyclohexane, was used as the diluent in the polymerization medium. The porous structure of the beads was found to be affected by the solvent composition used to dissolve the monomers initially. It was observed that the porosity and pore size increased gradually with the increase of cyclohexane content of the solvent composition. It was also detected that the pore radii changed from 2-10 nm to 700-1000 nm as the cyclohexane content of the diluent changed from nil to 100 % (v/v) respectively. These results indicate that pore size of the copolymer beads is a function of solvent composition.
Keywords: STYRENE-DIVINYLBENZENE COPOLYMERS; POLYMER PARTICLES; Polymer Science